The relationship between visfatin, resistin and CRP parameters and insulin resistance in obese and non-obese type 2 diabetic individuals - Yüksel, Arzu; Telci, Ayşe Gül Sündüs; Kubat Üzüm, Ayşe (The European Research Journal, 2025)
Objectives: Inflammation caused by adipokines such as adiponectin, leptin, resistin, visfatin, interleukin-6 (IL-6), and tumor necrosis factor-α (TNF-α) released by fat cells and immune cells within fat tissue is a significant factor in the onset of insulin resistance and Type 2 diabetes mellitus (T2DM). This study explores the relationship among these adipokines and insulin resistance in T2DM patients, focusing on the impact of abdominal obesity. Methods: The study involved 73 adult T2DM patients who were seperated into two groups based on their body mass index (BMI): 47 were classified as obese (BMI ≥30 kg/m²), and 26 were classified as non-obese (BMI <25 kg/m²). Additionally, 42 healthy controls were included, comprising 18 obese and 24 non-obese individuals. Adipokine concentrations (resistin, leptin, adiponectin, visfatin, IL-6 and TNF-α) were measured with the ELISA method. Results: The concentrations of adiponectin were substantially lower in T2DM patients relative to the control group (P<0.0125). Leptin concentrations did not show significant differences between the groups, but there was a notable increase in obese controls compared to non-obese controls (P<0.0125). TNF-α concentrations were significantly higher in obese controls than in non-obese controls (P<0.001). Resistin concentrations were significantly correlated with C-reactive protein (CRP) and IL-6 in both groups, independent of BMI (P=0.001 and P<0.0125, respectively). We found that CRP levels were significantly higher in both obese diabetics compared to non-obese diabetics and in obese controls compared to non-obese controls (P<0.0001). Conclusions: Adipose tissue is a crucial determinant of circulating inflammation markers. Elevated CRP concentrations in obesity may result from insulin resistance rather than being a cause. Further research is required to comprehend the connection between fatty tissue, insulin resistance, and elevated inflammatory markers.